ChemInform Abstract: The Polar Phase of Li2Ge4O9 at 298, 150 and 90 K. Issue 3 (21st January 2014) - Redhammer, Guenther J.; Tippelt, Gerold
Abstract The title compound is obtained by high‐temperature flux melting of stoichiometric amounts of Li2CO3, Al2O3, and GeO2 together with a 10‐fold excess of a flux consisting of 80 wt% Li2MoO4 and 20 wt% LiVO3 (Pt crucible, 1473 K, 12 h, cooling to 873 K with a rate of 3 K/h).